Effect of Shear Displacement on the Directivity of Permeability in 3D Self-Affine Fractal Fractures - Richeng Liu; Na Huang; Yujing Jiang; Hongwen Jing; Bo Li; Yuxuan Xia (Geofluids)
The effect of shear displacement on the directivity of permeability in fractures is studied in this paper. The studied fracture surface has 3D self-affine fractal characteristics that are created using the modified successive random addition (SRA) method. Fluid flow through the fracture is simulated using the COMSOL Multiphysics code based on the finite element method (FEM) by changing the angle between the shear direction and macroscopic flow direction. The evolutions of the aperture distribution and flow paths with changes in shear displacement are investigated, and the change in the equivalent permeability is evaluated. The results show that the mean aperture and its deviation for rough fractures increase as the shear displacement increases, and this change is accompanied by an increase in void spaces and decreasing contact areas between the upper and lower fracture surfaces. The flow paths become more tortuous, and the channeling flow effect occurs during the shear process. The equivalent permeability of the fractures varies as the inclination between the shear direction and macroscopic flow direction changes. The permeability with the largest magnitude exists in the direction perpendicular to the shear direction, and the permeability with the smallest magnitude exists in the direction parallel to the shear direction. The equivalent permeability of the fractures at other inclinations varies between the smallest and greatest values. Notably, larger inclinations correspond to higher permeability magnitudes. The ratio of the directional permeability to the permeability in the direction parallel to the shear direction varies between 1.03 and 2.71. This ratio tends to decrease as the shear displacement and JRC increase, which indicates that the directivity of the permeability is more obvious for fractures with smaller JRCs and smaller shear displacement.